Kinetic studies on waste cooking oil into biodiesel via hydrodynamic cavitation - Chuah, L.F. (Elsevier Ltd, 2017)
Development of cleaner biodiesel production related to hydrodynamic cavitation of methyl ester synthesis from sustainable waste cooking oil via alkali-catalysed transesterification is gaining importance due to considerable lower energy requirement and time. The effects of the oil to methanol molar ratio (1:4–1:7), catalyst concentration (0.5–1.25 wt ) and reaction temperature (50–65 °C) have been studied in a hydrodynamic cavitation and mechanical stirring system. Highest conversion of 98 was achieved under optimum conditions of 1:6 M ratio of oil to methanol, 1 wt potassium hydroxide as alkali catalyst, 60 °C and 15 min reaction time. It has been observed that yield efficiency and reaction time were 833 higher and 600 shorter using hydrodynamic cavitation compared to mechanical stirring. Triglycerides conversion obeys pseudo-first order mechanism. The kinetic parameters of hydrodynamic cavitation and mechanical stirring were calculated, where the reaction rate constants were 0.238 and 0.031 min−1, activation energies were 89.7 and 92.7 kJ/mol and the pre-exponential factors were 2.623 × 10​13 and 1.120 × 10​13 min−1. Hydrodynamic cavitation was 1.8 fold more energy efficient and 4.6 fold lower feedstock used per produced product than mechanical stirring in biodiesel production. In conclusion, waste cooking oil methyl ester produced via hydrodynamic cavitation proved to be time saving and energy efficient compared to mechanical stirring. This makes the process more environmental friendly using hydrodynamic cavitation. © 2016 Elsevier Ltd